Measurement of zinc stable isotope ratios in biogeochemical matrices by double-spike MC-ICPMS and determination of the isotope ratio pool available for plants from soil - Arnold,T; Schoenbaechler,M; Rehkaemper,M; Dong,S; Zhao,F-J; Kirk,GJD; Coles,BJ; Weiss,DJ (Analytical and Bioanalytical Chemistry, 2010)
Analysis of naturally occurring isotopic variationsis a promising tool for investigating Zn transport andcycling in geological and biological settings. Here, wepresent the recently installed double-spike (DS) techniqueat the MAGIC laboratories at Imperial College London.The procedure improves on previous published DS methodsin terms of ease of measurement and precisions obtained.The analytical method involves addition of a 64Zn–67Zndouble-spike to the samples prior to digestion, separation ofZn from the sample matrix by ion exchange chromatography,and isotopic analysis by multiple-collector inductivelycoupled plasma mass spectrometry. The accuracy andreproducibility of the method were validated by analysesof several in-house and international elemental referencematerials. Multiple analyses of pure Zn standard solutionsconsistently yielded a reproducibility of about ±0.05‰(2 SD) for δ66Zn, and comparable precisions were obtainedfor analyses of geological and biological materials. Highlyfractionated Zn standards analyzed by DS and standardsample bracketing yield slightly varying results, whichprobably originate from repetitive fractionation eventsduring manufacture of the standards. However, the δ66Znvalues (all reported relative to JMC Lyon Zn) for two lessfractionated in-house Zn standard solutions, Imperial Zn(0.10±0.08‰: 2 SD) and London Zn (0.08±0.04‰), arewithin uncertainties to data reported with different massspectrometric techniques and instruments. Two standardreference materials, blend ore BCR 027 and ryegrass BCR281, were also measured, and the δ66Zn were found to be0.25±0.06‰ (2 SD) and 0.40±0.09‰, respectively. Takentogether, these standard measurements ascertain that thedouble-spike methodology is suitable for accurate andprecise Zn isotope analyses of a wide range of naturalsamples. The newly installed technique was consequentlyapplied to soil samples and soil